Comparação entre testes IDGA (p26) e ELISA indireto (rgp 90) no diagnóstico da anemia infecciosa eqüina - Marilda Ferreira Martins (2004)
The ELISA (Enzyme Linked Immunosorbent Assay) using recombinant rgp90 (Reis, 1997) and classical test AGID (Agar Gel Immunodiffusion) p26 were compared in order to validate the ELISA for use in the diagnosis of EIA. We collected 1007 serum samples from horses in different regions of Minas Gerais in a total of 32 municipalities and 156 properties. The results of the ELISA based on areas of serological interpretation. Sera which had optical density (OD) smaller than 0.220 were considered negative and those who showed OD equal to or greater than 0.220 indeterminate (to .263) and positive ( 0.264). The AGID test detected 95 positive sera (9.4%) while the ELISA 128 (12.7%). Sensitivity comparison of the two tests was 97.81% and specificity of 96.16%. Ten animals in the negative and indeterminate AGID / ELISA positive were traced to a second collection (three of them with suggestive signs of EIA) and tested by ELISA, AGID, and DOT BLOT CELISA. An animal became positive in AGID (CELISA, DOT p26 and gp90 positive) and in the first examination was detected by ELISA. The ELISA showed 90 rgp be sensitive, specific and rapid and can be used as screening tests and surveys enable state officials